Assessments of practices, knowledge and determinant factors associated with habitual beverage consumption among undergraduate students in Universiti Sains Malaysia Health Campus, Kelantan - Xin, Hu Jia (Universiti Sains Malaysia, 2025)
High consumption of sugar-sweetened beverages (SSBs) is regarded as major determinants of non-communicable diseases (NCDs). Understanding the habitual beverage intake types and patterns and its associated dietary and lifestyle factors among young adults is important to prevent NCDs risk in later life. The main objective of the study was to determine habitual beverage intake and its association with demographic factors, body mass index (BMI), dietary and lifestyle practices, and self-perception of sweetness preference among 195 undergraduate students in Health Campus, University Science of Malaysia. The study also aimed to assess participants' knowledge regarding beverage intake. A pre-piloted beverage questionnaire of 30 beverage types were used to assess habitual beverage intake. Dietary practices and weekly physical activity levels were gathered. Self-perception of sweetness preference was evaluated by a 10-point Likert scale. A dehydration questionnaire and a pre-piloted beverage knowledge questionnaire were used to evaluate participants' knowledge. Average total beverage intakes of these participants were 2.32 liters, with non-SSBs consumed more than SSBs (2.1 vs. 0.3 L). Males had significantly higher intakes of carbonated drinks (P<0.001) and non-carbonated drinks (P<0.05) compared to the females. Mean difference in SSBs daily intake was significant when accounted for BMI (P = 0.025) and fast-food intake (P = 0.022). Non-SSBs and sport drink intake showed a significant association with physical activity level (P = 0.022 and P < 0.001 respectively). Sweetness preference showed a weak positive correlation with SSBs intake (P = 0.002, rs = 0.214). The findings highlight gender differences in the consumption patterns of soft drinks. High SSBs intake was driven by unhealthy dietary practices and higher sweet taste preference. Non-SSBs and sport drinks consumption was significantly associated with physical activity. These highlight the need for effective targeted public health strategies to encourage healthy beverage consumption behaviors among collegiate students.